Theabrownin Inhibits Cell Cycle Progression and Tumor Growth of Lung Carcinoma through c-myc-Related Mechanism - Zhou, Li; Wu, Feifei; Jin, Wangdong; Yan, Bo; Chen, Xin; He, Yingfei; Yang, Weiji; Du, Wenlin; Zhang, Qiang; Guo, Yonghua; Yuan, Qiang; Dong, Xiaoqiao; et al. (Frontiers in Pharmacology, 2017)
Green tea, the fresh leaves of Camellia sinensis, is not only a health-promoting beverage but also a traditional Chinese medicine used for prevention or treatment of cancer, such as lung cancer. Theabrownin (TB) is the main fraction responsible for the medicinal effects of green tea, but whether it possesses anti-cancer effect is unknown yet. This study aimed to determine the in vitro and in vivo anti-lung cancer effect of TB and explore the underlying molecular mechanism, by using A549 cell line and Lewis lung carcinoma-bearing mice. In cellular experiment, MTT assay was performed to evaluate the inhibitory effect and IC50 values of TB, and flow cytometry was conducted to analyze the cell cycle progression affected by TB. In animal experiment, mice body mass, tumor incidence, tumor size and tumor weight were measured, and histopathological analysis on tumor was performed with TUNEL staining. Real time PCR and western blot assays were adopted to detect the expression of C-MYC associated genes and proteins for mechanism clarification. TB was found to inhibit A549 cell viability in a dose- and time-dependent manner and block A549 cell cycle at G0/G1 phase. Down-regulation of c-myc, cyclin A, cyclin D, cdk2, cdk4, PCNA and up-regulation of p21, p27, and PTEN in both gene and protein levels were observed with TB treatment. A c-myc-related mechanism was thereby proposed, since c-myc could transcriptionally regulate all other genes in its downstream region for G1/S transitions of cell cycle and proliferation of cancer cells. This is the first report regarding the anti-NSCLC effect and the underlying mechanism of TB on cell cycle progression and proliferation of A549 cells. The in vivo data verified the in vitro result that TB could significantly inhibit the lung cancer growth in mice and induce apoptosis on tumors in a dose-dependent manner. It provides a promising candidate of natural products for lung cancer therapy and new development of anti-cancer agent.